2017
DOI: 10.1007/s10552-017-0905-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index and non-Hodgkin lymphoma risk in an Italian case–control study

Abstract: Background While dietary factors have been shown to play an important etiologic role in non-Hodgkin lymphoma (NHL), little is known about the association between inflammatory properties of diet and NHL risk. Methods We explored the association between the dietary inflammatory index (DII) and NHL risk in a multicentric Italian case-control study conducted between 1999 and 2014. Cases were 536 subjects with incident, histologically confirmed NHL from 3 areas in Italy. Controls were 984 subjects admitted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…In addition, several studies have consistently linked chronic inflammation or autoimmune conditions with lymphomagenesis and reported associations between plasma levels of cytokines, or other inflammatory markers, and lymphoma . Recent studies are supporting the inflammatory potential of diet; in particular, for lymphoid neoplasms, positive associations have been recently reported between a proinflammatory dietary score and NHL . Thus, the MD's favorable fatty acid profile, as well as a high intake of fiber, vitamins and flavonoids, may be relevant owing its properties.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, several studies have consistently linked chronic inflammation or autoimmune conditions with lymphomagenesis and reported associations between plasma levels of cytokines, or other inflammatory markers, and lymphoma . Recent studies are supporting the inflammatory potential of diet; in particular, for lymphoid neoplasms, positive associations have been recently reported between a proinflammatory dietary score and NHL . Thus, the MD's favorable fatty acid profile, as well as a high intake of fiber, vitamins and flavonoids, may be relevant owing its properties.…”
Section: Discussionmentioning
confidence: 98%
“…[40][41][42] Recent studies are supporting the inflammatory potential of diet 43 ; in particular, for lymphoid neoplasms, positive associations have been recently reported between a proinflammatory dietary score and NHL. 44 Thus, the MD's favorable fatty acid profile, as well as a high intake of fiber, vitamins and flavonoids, may be relevant owing its properties.…”
Section: Discussionmentioning
confidence: 99%
“…The “dietary inflammatory index” (DII) weights each major macronutrient and multiple micronutrients on the basis of their general proinflammatory effects, as measured, for example, by assessment of C-reactive protein in serum [ 63 ]. This index significantly correlates with the risk of developing postmenopausal breast cancer, colorectal cancer, lung cancer in smokers, non-Hodgkin lymphoma, bladder cancer, and nasopharyngeal carcinoma [ 70 75 ].…”
Section: Sources and Modulators Of Inflammagingmentioning
confidence: 99%
“…Clear associations have been reported for colorectal cancers [51,52] and gastric cancers [53], whereas the association with breast cancer is still inconclusive [54][55][56]. Regarding haematological cancers, other case-control studies looking into the association of DII (and DII-like tools) and other types of haematological cancers have been carried out [37,38], reporting positive associations between a pro-inflammatory diet and NHL and B-cell lymphoma subtypes. These findings were supported by the European Prospective Investigation into Cancer and Nutrition (EPIC) study for NHL and all mature B-cell subtypes [36].…”
Section: Discussionmentioning
confidence: 99%
“…This study, including 2606 non-Hodgkin lymphoma (NHL) cases and 537 CLL cases, used a modified version of the DII and showed no association between the inflammatory score of the diet and overall lymphoma as well as CLL risk [36]. In a couple of Italian case-control studies, DII has been shown to be associated with Non-Hodgkin's Lymphoma but not with Hodgkin's Lymphoma [37,38].…”
Section: Introductionmentioning
confidence: 88%